Selenium Concentrations In Lentil Seeds From Bengal - Gangetic Plains (India) Including Arsenic-Contaminated Zones (Applied Biological Research, 2013)
Seed selenium (Se) concentrations of 22 genotypes (21 cultivars and one local  check) of lentil (Lens culinaris Medik.), grown in different parts of West Bengal  (India) including arsenic-affected areas, were estimated. Se content varied  significantly in genotypes with highest (167 µg Se kg-1) and lowest (9 µg Se kg-1)  content in cv. ‘Pusa 4’ and ‘VL Massor 44’, respectively. The 9 genotypes grown  in arsenic-prone areas showed deficient Se levels. However, ‘Pusa 1’, ‘Pusa 6’,  ‘JLS 1’, ‘Sehore 74-3’, ‘VL Masoor 44’ and ‘VL Masoor 103’ exhibited increased  Se levels when grown outside the As-contaminated zones, indicating possible  inhibition of Se uptake by As. Marginal variations in Se content in genotypes ‘B  17’, ‘PL 406’ and ‘S 256’ between As-contaminated and non-contaminated areas  suggested genotype-dependent accumulation of Se.
Keywords: Arsenic; lentil; nutritional improvement; seed; selenium